Key factors that influence allied health professional therapists to remain working within a stroke unit. - Mandri, Catherine; Reed, Debbie (Advanced Journal of Professional Practice, 2025)
The National Health Service is experiencing significant workforce shortages due to lack of adequate workforce planning. Stroke units (SUs) needs to retain highly skilled staff to deliver specialised services. Currently in the Southeast of England, workforce retention issues pose a high operational risk within stroke services. This case study completed semi-structured interviews of occupational therapists, physiotherapists, and speech and language therapists, termed Allied Health Professional Therapists (AHPTs), with the aim to provide up-to-date insights into key retention factors. Recruitment was via purposive selection and ethical approval was gained from the Research Ethics Advisory Group of [University]. Thematic analysis and verification techniques of member checking and inter-rater reliability were completed. Four key factors arose: 1) multi-faceted development system; 2) driving change; 3) intrinsic value; and 4) extrinsic motivators, overarched by personal evolution. Interconnection of the factors anchored AHPTs within SU retention and each factor’s importance was unique to individuals and fluid in nature.